(untitled) (Palestine Technical College Journal for Research and Studies, 2022)
This study aims to examine the obstacles of practicing change leadership among principals of governmental schools in Jerusalem city from their point of view, and also to reveal if there are any statistically significant differences at level (0.05 ≥α) between the averages of sample members’ estimation of the obstacles of practicing change leadership among principals to be attributed to the following variables: (sex, years of service as a school principal, the educational stage of the school, and the number of training courses). By using the descriptive/analytical approach, and by referring to previous literature, a questionnaire which consists of (59) paragraphs distributed to (4) fields was designed. These fields are: administrative obstacles, human obstacles, technical obstacles, and financial obstacles, and after verifying the questionnaire’s validity and reliability, it was applied to a sample consists of (45) male and female principals. The study concluded that the total estimation degree of the obstacles of practicing change leadership among principals was “high”. The results also indicated that there are statistically significant differences between the averages of sample members’ estimations to be attributed to (sex) variable (concerning the questionnaire as a whole and the fields of administrative obstacles and technical obstacles) in favor of principals. The results also revealed that there are statistically significant differences to be attributed to the school’s educational stage, and differences between lower basic stage and higher basic stage were in favor of lower basic stage, and between secondary education stage and higher basic stage were in favor of secondary education stage. The results also showed that there are no statistically significant differences between the averages of sample members’ estimations to be attributed to the variables (years of service as a school principal) and (the number of training courses).